Continuing Challenges and Potential for Collaborative Approaches to Education Reform - Bodilly, Susan J. (RAND Corporation, 2011)
The Ford Foundation's Collaborating for Education Reform Initiative (CERI) provided grantees with funds, guidance, and technical assistance to develop collaboratives and carry out activities to improve teaching and learning. A second effort, CERI 2, laid down a new set of goals for grantees. RAND Corporation researchers evaluated the initiative.